PENGARUH KOMPETENSI, INDEPENDENSI, DAN MOTIVASI AUDITOR TERHADAP KUALITAS AUDIT - Ichrom, Mochamad; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This main aims of this study is to test whether Competency, Independency, and Motivation auditors affect theAudit quality. The sample collection technique has been carried out by using purposive sampling. The result ofthe research shows that there is a variable competency, independency, and motivation variables are used by theresearcher. When the competency and motivation of an auditor is getting high, the audit quality which isgenerated by the auditor is getting better. When the perception of the respondent to the independency is gettinghigh, it can make the declination to the audit quality which is generated by the auditor.Keywords: Competency, Independency, Motivation, and Audit Quality.